Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1007/s12576-011-0184-5
|View full text |Cite
|
Sign up to set email alerts
|

Leptin resistance does not induce hyperphagia in the rat

Abstract: Leptin has been thought to work as a mediator for body weight control by inhibiting food intake. Leptin, however, cannot prevent obesity induced by a high-fat diet (HFD) probably because of leptin resistance. We investigated daily feeding and weight gain when ordinary chow (OC) was changed to a HFD in male rats. Food intake, by weight, significantly increased the next day, but gradually decreased until at 20 days the HFD intake contained the same calories as consumed by the OC-fed control rats. The reduction i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…First, it was observed that HFD was able to influence the pattern of food and drink intake of animals. Although highly palatable [41], we observed a reduction in HFD consumption in relation to the standard diet, which is in agreement with the findings of Higuchi et al [42]. The lower intake (g) of HFD may be related to its energy density, in which it has approximately 50% more calories than the standard diet.…”
Section: Discussionsupporting
confidence: 92%
“…First, it was observed that HFD was able to influence the pattern of food and drink intake of animals. Although highly palatable [41], we observed a reduction in HFD consumption in relation to the standard diet, which is in agreement with the findings of Higuchi et al [42]. The lower intake (g) of HFD may be related to its energy density, in which it has approximately 50% more calories than the standard diet.…”
Section: Discussionsupporting
confidence: 92%
“…3A). Both groups of mice showed no significant difference in the total amount of calories consumed (16,17) (Fig. 3B).…”
Section: High Fat Diet-accelerated Src Kinase-induced Prostate Tumorsmentioning
confidence: 92%
“…D12450Bi; Research Diets, New Brunswick, NJ), and 36 mice were placed on HFD with 60% of calories coming from fat (catalog D12492i, Research Diets) for the duration of the study. Both diets have been formulated specifically for scientific research and have been used widely in research with rodents [ 14 16 ]. Dietary components of the diets used in this study can be found in Supplemental Table S1 (Supplemental Data are available online at www.biolreprod.org ).…”
Section: Methodsmentioning
confidence: 99%